Quetiapine Inhibits Microglial Activation by Neutralizing Abnormal STIM1-Mediated Intercellular Calcium Homeostasis and Promotes Myelin Repair in a Cuprizone-Induced Mouse Model of Demyelination - Wang, Hanzhi; Liu, Shubao; Tian, Yanping; Wu, Xiyan; He, Yangtao; Li, Chengren; Namaka, Michael; Kong, Jiming; Li, Hongli; Xiao, Lan (Frontiers in Cellular Neuroscience, 2015)
Microglial activation has been considered as a crucial process in the pathogenesis of neuro-inflammation and psychiatric disorders. Several antipsychotic drugs have been shown to display inhibitory effects on microglial activation in vitro, possibly through the suppression of elevated intracellular calcium (Ca2+) concentration. However the exact underlying mechanisms still remain elusive. In this study, we aimed to investigate the inhibitory effects of quetiapine (Que), an atypical antipsychotic drug, on microglial activation. We utilize a chronic cuprizone (CPZ)-induced de-myelination mouse model to determine the direct effect of Que on microglial activation. Our results show that treatment with Que significantly reduced recruitment and activation of microglia/macrophage in the lesion of corpus callosum and promoted re-myelination after CPZ withdraw. Our in vitro studies also confirm the direct effect of Que on lipopolysaccharide (LPS)-induced activation of microglial N9 cells whereby Que significantly inhibited the release of nitric oxide (NO) and tumor necrosis factor α (TNF-α). Moreover, we demonstrated that pre-treatment with Que, neutralized the up-regulation of STIM1 induced by LPS and declined both LPS and thapsigargin (Tg)-induced store operated Ca2+ entry (SOCE). Finally we found that pre-treatment with Que significantly reduced the translocation of nuclear factor kappa B (NF-κB) p65 subunit from cytoplasm to nuclei in LPS-activated primary microglial cells. Overall, our data suggested that Que may inhibit microglial activation by neutralization of the LPS-induced abnormal STIM1 mediated intercellular calcium homeostasis.